THE IMPACT OF ELECTRIC VEHICLE ADOPTION BARRIERS ON CONSUMER DOUBT AND PURCHASE INTENTIONS IN THAILAND - Arti Pandey; Haonan Li (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Abstract: This study examines how obstacles in Thailand’s electric vehicle market reshape consumer psychology and reduce readiness to buy by integrating the Technology Acceptance Model with the Theory of Planned Behavior into a single path where price burden, infrastructure gaps, technical uncertainty and policy opacity elevate perceived risk, recast usefulness and ease beliefs, weaken attitudes and perceived control, and thereby depress intention. A structured questionnaire in Thai, English, and Chinese produced four hundred valid responses from prospective buyers recruited through convenience sampling, the instrument underwent translation and back translation with a pilot of thirty cases, and robust reliability and validity checks supported subsequent regression tests. Results indicate that financial, technical, and charging constraints significantly increase consumer doubt, that doubt is a strong negative predictor of purchase intention, and that barriers retain a direct association with intention, revealing partial rather than complete mediation. The findings enrich adoption theory by situating doubt within a stimulus organism response sequence and offer practical guidance for finance, warranty communication, and dependable public and workplace charging that together improve perceived control and reduce anxiety. Keywords: Electric vehicles, Consumer doubt, Adoption barriers, Purchase intention, Technology Acceptance Model, Theory of Planned Behavior, Thailand